Thank you for the opportunity to help you with your question!

4x+3y=-9-----------(1)

x-2y=-5--------------(2)

from (2)

x=2y-5--------------(3)

substitute for x in (1) form (3)

4(2y-5)+3y=-9

remove brackets

8y-20+3y=-9

simplify

11y=11

y=1

from (1)

4x+3(1)=-9

4x=-9-3

4x=-12

x=-12/4

x=-3

so y = 1 and x= -3

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up